2021
DOI: 10.3389/fcimb.2021.640707
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterial Growth Inhibition Assay (MGIA) as a Host Directed Diagnostic Tool for the Evaluation of the Immune Response in Subjects Living With Type 2 Diabetes Mellitus

Abstract: The lack of efficient and cost-effective diagnostic tools contributes to poor control of tuberculosis in endemic countries. Moreover, host biological processes influence susceptibility, and infection resolution. It is well known that comorbidities such as type 2 diabetes mellitus (DM2) affect the host immune response, making individuals more susceptible to Mycobacterium tuberculosis infection. Currently, there are no laboratory tools that can identify those subjects who have a higher risk of developing the dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…applied the direct whole blood MGIA to evaluate the immune response in patients with type-2 diabetes mellitus (DM2) with optimal and poor glycaemic control ( 99 ). They found significantly reduced control of M.tb H37Rv growth among DM2 patients compared with healthy volunteers, and among DM2 patients with poor glycaemic control (but not those with optimal glycaemic control) compared with healthy volunteers ( 99 ). This is consistent with the well-documented increased risk of TB in DM2 patients, particularly those with poor glycaemic control.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…applied the direct whole blood MGIA to evaluate the immune response in patients with type-2 diabetes mellitus (DM2) with optimal and poor glycaemic control ( 99 ). They found significantly reduced control of M.tb H37Rv growth among DM2 patients compared with healthy volunteers, and among DM2 patients with poor glycaemic control (but not those with optimal glycaemic control) compared with healthy volunteers ( 99 ). This is consistent with the well-documented increased risk of TB in DM2 patients, particularly those with poor glycaemic control.…”
Section: Resultsmentioning
confidence: 99%
“…This is consistent with the well-documented increased risk of TB in DM2 patients, particularly those with poor glycaemic control. The authors point to the potential utility of the direct whole blood MGIA as an in vitro marker of M.tb control in vivo in DM2 patients, and as a tool for evaluating individual mycobacteria-specific immune responses to inform host-directed therapy selection ( 99 ). Kewcharoenwong et al.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, using a model of in vitro granulomas generated by DM2 patients' peripheral blood mononuclear cells infected with M. bovis BCG, the authors observed that PBMCs from GSH-supplemented patients produced enhanced levels of IFN-γ and controlled bacterial replication more efficiently than those from placebo-treated patients ( 30 ). In particular, the levels of IFN-γ were markedly reduced in samples from patients with poor glycemic control, which also failed to inhibit bacterial growth ( 31 ). Thus, the different immune responses involved in IFN-γ between TB with DM and without DM may be due not only to differences in the frequencies of innate and adaptive immune cells but also to uncontrolled hyperglycaemia.…”
Section: Discussionmentioning
confidence: 99%